BEHIND THE WALLS - Exploring how architecture can be a mode of inquiry on questions of intimate partner violence. - Rajabi Gajin, Hoda (My University, 2023)
Every three weeks, a woman is killed by a man in Sweden. In 2021, 38 300 crimes of assault and 8 600 rapes against women and girls were reported which is more than one rape per hour per year. “ In 19 cases of the confirmed cases of lethal violence in 2021, victims and perpetrators were related by a close relationship (partner or ex-partner), which accounted for 17 percent of all cases of lethal violence. In 2020, the corresponding number was 17 cases (14%)” (Brå, n.d., para. 6). There are many different types of men’s violence against women in an intimate partner relationship. Intimate partner violence (IPV) has a variety of meanings for different researchers. For purposes of this thesis, the definition used for IPV will be defined as any type of violence that happens in an intimate partner relationship. The victim and perpetrator have a history of close relationships with each other as a spouse or partner. The question asked in this thesis is: How can ethnographic work and architectural design methods make architecture discipline engage with questions on non-physical violence in intimate partner relationships? In order to answer this question, the theoretical aim has been to understand the psychology of abuse and find behaviors in an intimate partner relationship that causes violence. Its applied purpose has been to explore in which way architectural design can contribute to preventing and intervening in violence. By exploring a design approach that enables speculative visualization that tells narratives of sensitive subjects, the hope is to raise awareness among women and young girls in order to empower them in society. The studies led to the creation of a methodology working with spatial narratives and collecting stories to unveil and contextualize them. This included creative workshops using architectural instruments such as drawings, clay, surveys, etc. to gather personal experiences with intimate partner violence.